Mapping Sustainable Finance: A Detailed Analysis of Banks in Indonesia - Inten Meutia; Shelly Febriana Kartasari; Zulnaidi Yaacob; Murugesh Arunachalam (Indonesian Journal of Sustainability Accounting and Management, 2020)
This study aims to map the conformity of sustainability reports (SRs) for the BUKU 3 and BUKU 4 bank groups with regulations issued by the Indonesian Financial Services Authority (OJK). The research is exploratory, considering that FSA Regulation number 51 of 2017 was not applied until 2019. It represents a quantitative descriptive study employing a content analysis approach to explore and analyze data and factual input from SRs. The data used are drawn from the 2017 report concerning seven BUKU 3 banks and five BUKU 4 banks. This study found that the contents of the bank reports, with the components required by POJK number 51 of 2017, concerning the sustainable financial action plan and the SR, did not fully meet the requirements of the POJK. Using cross-tabulation analysis, we found that the average bank has a good, sustainable financial action plan and suitable sustainability reporting above 90%. It also has higher total assets, CAR/KPPM, ROA, and ROE ratios than banks with lower index suitability. This finding implies a potential relationship between SR compliance levels and bank financial characteristics. Overall, the conformity level of BUKU 4 banks is better than that of BUKU 3 banks.